Cosmetic Remodeling of the Smile: Combining Composite Resin and Ceramics over Teeth and Implants - Leonardo Fernandes da Cunha; Ubiracy Gaião; Rafael Coutinho Silva; Carla Castiglia Gonzaga; Gisele Maria Correr (Hindawi Limited, 2017)
The aim of this paper is to describe a restorative approach to the cosmetic remodeling of the teeth of a young adult patient with right maxillary lateral hypodontia and left lateral microdontia. A conservative restorative management was proposed to improve smile esthetics by combining direct composite resins and ceramics. Initially, periodontal therapy and dental bleaching were performed. Subsequently, direct composite resins were applied to the central incisors and canines to reestablish the sizes and shapes of these teeth. Finally, ceramics were placed on the implant and the microdontia to unite with the new alignment and color of the anterior teeth. Thus, conservative remodeling to improve the harmony of the smile was provided.